Analysis of the performance of pontoon-type floating breakwaters. Issue 1 (2nd January 2017) - Moghim, Mohammad Navid; Botshekan, Meshkat
ABSTRACT: The transmission coefficient of floating breakwater (FB) is the most important index for gauging their efficiency. It depends on sea state conditions such as incident wave height, wave period, water depth and structural parameters such as the draught and width of the FB. In this study, dimensionless parameters are developed to predict the value of the transmission coefficient. Since the wave excites the motion responses of the FB, it acts like a wave generator. In this paper, dimensionless parameters that are related to the incident wave height and wave length to predict the sway and heave motion of the FB are proposed. The study is based on a total of 167 data extracted from experiments carried out by various researchers.